Rancang Bangun Smart Sensor Television Berbasis Atmega32 - Widdha Mellyssa (Smart Techno (Smart Technology, Informatics and Technopreneurship), 2019)
Watching television at close range can be bad for eye health such as nearsightedness (myopia). Watching television with a distance of less than 5 times the diagonal of the television can have adverse effects on the health of the eye lens such as nearsightedness, photochemical injuries, and astigmatism. Damage to the lens of the eye is caused by the blue light emitted by the television. Therefore, an ATMega32-based Smart Sensor Television Design Tool was created, which is an automatic television viewing distance detector as an effort to maintain eye health while watching television. In watching television, there are several rules that must be obeyed so that the bad effects of television blue light do not come to us. One of them is the distance of the television monitor screen to the eye must follow the applicable standard calculations. If the distance rules are violated, eye health can be threatened.